2015
DOI: 10.1039/c5nr00095e
|View full text |Cite
|
Sign up to set email alerts
|

Charged group surface accessibility determines micelleplexes formation and cellular interaction

Abstract: Micelleplexes are a class of nucleic acid carriers that have gained acceptance due to their size, stability, and ability to synergistically carry small molecules. MicroRNAs (miRNAs) are small non-coding RNA gene regulator that is consists of 19–22 nucleotides. Altered expression of miRNAs plays an important role in many human diseases. Using a model 22-nucleotide miRNA sequence, we investigated the interaction between charged groups on the micelle surface and miRNA. The model micelle system was formed from met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 42 publications
1
15
0
Order By: Relevance
“…The period of rapid elimination of VE822 (half-life of 2 hr, more rapid than the clearance rate of free drug) is due to elimination of NPs containing VE822, whereas the sustained levels are the result of a competition between slow VE822 release from the remaining intracellular NPs, elimination of free VE822, and slow elimination/degradation of the remaining NPs. We still have work to do in determining the relative contributions of these multiple routes for elimination in the tumor microenvironment, but recent experiments suggest that some of these mechanisms can be manipulated by changing properties of the NP, such as surface chemistry (5961). Still, even with our present formulation, NP-VE822 was able to maintain intracranial drug levels above the IC50 of VE822 (0.125uM) for at least 10 d after administration.…”
Section: Discussionmentioning
confidence: 99%
“…The period of rapid elimination of VE822 (half-life of 2 hr, more rapid than the clearance rate of free drug) is due to elimination of NPs containing VE822, whereas the sustained levels are the result of a competition between slow VE822 release from the remaining intracellular NPs, elimination of free VE822, and slow elimination/degradation of the remaining NPs. We still have work to do in determining the relative contributions of these multiple routes for elimination in the tumor microenvironment, but recent experiments suggest that some of these mechanisms can be manipulated by changing properties of the NP, such as surface chemistry (5961). Still, even with our present formulation, NP-VE822 was able to maintain intracranial drug levels above the IC50 of VE822 (0.125uM) for at least 10 d after administration.…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs are known to be involved in cancer progression, invasion and metastasis wherein their levels are either upregulated or down regulated. miRNAs as therapeutic tool in cancer has been explored by several research groups which have shown improved outcome in terms of increased cytotoxicity, decreased invasion and metastasis. ,,, Delivery strategies including nanoplexes, polyplexes, lipoplexes, micelleplexes , and dendriplexes have been reported for miRNA delivery since naked miRNAs could not penetrate the bilayer lipidic membrane because of high molecular weight, hydrophilic and anionic nature and instability in biological milieu. Apart from effectively complexing miRNAs and protecting them from degradation, another important requirement for ideal delivery system is that they should be able to improve the uptake of miRNA by cancer cells followed by their successful endosomal escape and release into the cytoplasm so that they can get into the RISC assembly for effective mRNA degradation and/or translation repression …”
Section: Discussionmentioning
confidence: 99%
“…Micelles and micelleplexes were prepared as previously reported by our group. 34 Briefly, 10 mg of block copolymer was dissolved in 0.5 mL of acetonitrile. Solvent was removed by rotovap to form a polymer film.…”
Section: Methodsmentioning
confidence: 99%
“…30−33 The anti-miRNAs were complexed with the micelles, forming micelleplexes with the expectation that the anti-miRNA would complex with R 15 in the hydrophilic corona through electrostatic interactions. 34,35 To facilitate the dissociation of the micelleplexes after cellular entry, we sought to exploit the reducing potential of the cell used to defend against oxidative stress. 36,37 In particular, intracellular glutathione (GSH) concentration (∼10 mM) is significantly higher than the level in the extracellular environment (less than 2 μM), 38 leading to significant glutathione-based reduction intracellularly serving as a trigger for drug delivery.…”
Section: ■ Introductionmentioning
confidence: 99%